2018
DOI: 10.4301/s1807-1775201815007
|View full text |Cite
|
Sign up to set email alerts
|

Towards classifying sociocultural aspects in global software development

Abstract: The geographical, temporal distances and socio-cultural differences are the biggest challenges for Global Software Development (GSD). In GSD, it is necessary to deal with behaviors, values and skills of the team members, conflicts, rework, delays, etc. can influence a software production process. The objective of this paper is to identify the sociocultural aspects and propose a classification structure under different analytical perspectives in order to offer adequate support to the management of GSD teams. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
(24 reference statements)
0
1
0
1
Order By: Relevance
“…Iriarte and Bayona 62 conducted a systematic literature review of soft skills in IT project success, which showed the importance of the role of project managers in the performance of a project. Massago et al (2018) through a systematic mapping try to identify the sociocultural aspects that can influence a software production process. The objective of this paper was to propose an approach that classifies aspects in three perspectives: collaboration, people, and external, which allows the project manager to make decisions about the performance of human resources and mitigate problems arising from communication, cooperation, and coordination, generating better results in indicators of productivity, quality, and efficiency of GSD teams.…”
Section: Related Workmentioning
confidence: 99%
“…Iriarte and Bayona 62 conducted a systematic literature review of soft skills in IT project success, which showed the importance of the role of project managers in the performance of a project. Massago et al (2018) through a systematic mapping try to identify the sociocultural aspects that can influence a software production process. The objective of this paper was to propose an approach that classifies aspects in three perspectives: collaboration, people, and external, which allows the project manager to make decisions about the performance of human resources and mitigate problems arising from communication, cooperation, and coordination, generating better results in indicators of productivity, quality, and efficiency of GSD teams.…”
Section: Related Workmentioning
confidence: 99%
“…Uma delas é o idioma inglês (Burzynski, Graeml, & Balbinot, 2010). Outra é a influência de aspectos socioculturais, como mostra o estudo de Massago et al (2018) sobre o desenvolvimento distribuído de softwares.…”
Section: Internacionalização De Empresas De Softwareunclassified